Association between NAG-B and cadmium in urine with no evidence of a threshold. Issue 3 (March 1995) - Bernard, A; Thielemans, N; Roels, H; Lauwerys, R
Abstract : OBJECTIVES--To explore the significance of the increase in urinary excretion of the lysosomal enzyme beta-N-acetylglucosaminidase (NAG) at low exposures to cadmium (Cd) that is frequently found in the absence of any other sign of renal dysfunction. METHODS--The activity was measured of the two main isoenzymes of NAG (NAG-A secreted by exocytosis and NAG-B released with cell membranes) in the urine of 49 male workers employed in a Cd smelter and of 20 age matched controls. RESULTS--An increased urinary excretion of low molecular weight proteins was noted only in subjects who excreted > 10 micrograms Cd/g creatinine. The urinary activity of NAG-B showed a dose related increase that was already significant in the group excreting 0.5-2 micrograms Cd/g creatinine. In multiple regression analysis the NAG-B activity correlated with the excretion of Cd but not with that of lead or mercury. The NAG-A activity was by contrast unaffected by exposure to Cd but correlated with the urinary excretion of lead and copper. CONCLUSIONS--As NAG-B is considered to be the lesional form of NAG, the existence of a specific association between this enzyme and urinary Cd excretion with no detectable threshold suggests that this metal produces cellular alterations at exposures commonly found in the general population.